Think like a monk : train your mind for peace and purpose every day - Shetty, Jay (New York : Simon & Schuster, 2020)
"Jay Shetty, social media superstar and host of the #1 podcast On Purpose, distills the timeless wisdom he learned as a monk into practical steps anyone can take every day to live a less anxious, more meaningful life"--
Includes bibliographical references and index.
Keywords: Self-realization.; Meaning (Psychology); Conduct of life; Hindu monastic and religious life